2018
DOI: 10.1002/bmc.4423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of mirabilite on the absorption and pharmacokinetics of the ingredients in Dahuang‐mudan decoction by a validated UPLC/QTOF–MS/MS method

Abstract: Dahuang-mudan decoction (DMD) has been widely used for disease treatment in China for 1700 years. The formula consists of Rhubarb, moutan bark, Prunus persica, wax gourd kernel and mirabilite, which have been well studied by multidisciplinary approaches. However, the role of the mineral mirabilite in DMD is unclear. The objective of this study was to investigate the effects of mirabilite on the absorption and pharmacokinetics of the ingredients in DMD. The constituents were identified in DMD extract and the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… Last but not least, the multiple components might raise a concern about the absorption and bioavailability of the PX formula. Lines of evidence have demonstrated that mirabilite could alter the pharmacokinetic behaviors of herb components by orchestrating the absorption of each compound [ 56 ]. Consistently, RNA sequencing corroborated that the PX formula modulated the cytochrome P450 system, the key enzyme responsible for drug metabolism [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“… Last but not least, the multiple components might raise a concern about the absorption and bioavailability of the PX formula. Lines of evidence have demonstrated that mirabilite could alter the pharmacokinetic behaviors of herb components by orchestrating the absorption of each compound [ 56 ]. Consistently, RNA sequencing corroborated that the PX formula modulated the cytochrome P450 system, the key enzyme responsible for drug metabolism [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhubarb (12 g), cortex moutan (9 g), semen persicae (12 g), wax gourd kernel (30 g) and mirabilite (9 g) were weighed and thoroughly mixed in water to prepare the DMD according to the methods described in our previous study (Nong et al, 2019). The final concentration of the prepared DMD was 1.5 g/ml (crude drugs/decoction).…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has existed for a thousand years and has been widely used in the treatment of various diseases (Layne & Ferro, 2017). Dahuang–Mudan decoction (DMD), a well‐known formulation composed of rhubarb, moutan bark, Prunus persica , wax gourd kernel and mirabilite, is described in the Synopsis of Prescriptions of the Golden Chamber (Nong et al, 2019). DMD has been widely used to treat intestinal carbuncle, which is associated with various gastrointestinal diseases including IBD, acute appendicitis and adhesive intestinal obstruction (Huang & Wang, 2008; Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological effects on appendicitis, inflammatory bowel disease, pelvic inflammatory disease and acute pancreatitis have been found with the identification of active compounds, emodin, aloe-emodin, rhein, paeoniflorin and amygdalin. Nong et al reported that Natrii Sulfas decreases the C max and AUC of emodin and rhein while increasing the absorption of aloe-emodin, indicating novel insight into the role of Natrii Sulfas in DMD in addition to a stool softener treatment of archenteric inflammatory disease (Zhang Y. X. et al, 2013;Nong et al, 2019).…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…For the formula Dahuang-mudan decoction (DMD), in which Rhei Radix et Rhizoma is combined with Magnoliae Officinalis Cortex, Aurantii Fructus Immaturus, and Natrii Sulfas, Zhang reported that the prolonged elimination of aloe-emodin and emodin, indicating a lower toxicity in this formula. The underlying mechanisms may be due to competitive inhibition between the chemical compounds in DMD and need to be further investigated (Nong et al, 2019). An eight-herb formula Niu-Huang-Jie-Du tablets (NHJDT), including Bovis Calculus (Niuhuang), Rhei Radix et Rhizoma, Realgar (As 2 S 2 , Xionghuang), Gypsum Fibrosum (CaSO 4 •2H 2 O, Shigao), Platycodonis Radix (Jiegeng), and Borneolum Syntheticum (D-borneoland, Bingpian), exerts heat-clearance and detoxicification in Chinese medicine.…”
Section: Drugsmentioning
confidence: 99%